Proposals of cardiorespiratory fitness classification in children and adolescents: literature review - Gabriel Bergmann; Mauren Bergmann; Rodrigo Moreira; Eraldo Pinheiro; Alexandre Marques; Pedro Hallal; Adroaldo Gaya (Revista Brasileira de Atividade Física e Saúde)
The aim of this study was to evaluate the procedures for the creation of cardiorespiratory fitness (CRF) cutoff points for children and adolescents. A search in Medline/Pubmed, Web of Science, Scopus, Lilacs, Scielo, and Google Scholar electronics database was performed. The keywords were used in English and Portuguese language. Inclusion criteria were: a) have been published as a full paper; b) have been published until December 2011; c) have as an aim to propose a cutoff point for cardiorespiratory fitness of children and/or adolescent or to present the procedure used by institutions to propose these cutoff points proposed; and d) the proposed cutoff points should be specific for healthy children and/or adolescent. The electronic search resulted in 10 documents. Two documents presented the procedures of institutions to propose cutoff points and eight presented originals proposals. Among the originals proposals, seven used the ROC curve as methodological procedure. For laboratory measures of CRF, methodologically consistent propositions of cutoff points were found. For the field tests, methodologically consistent cutoff points are available for the 9 minutes run/walk (9-min) test and 20 meters shuttle run test (20-m) for children and adolescents aged 07 to 12 and 10 to 18 years old respectively. In summary, laboratory measurements as well as some field tests have cutoff points elaborated with adequate methodological approaches for the assessment of the CRF of children and adolescents.